A Framework for Modelling the Electronic Medical Record - Rector, A. L.; Nowlan, W. A.; Kay, S.; Goble, C. A.; Howkins, T. J. (Methods of Information in Medicine, 1993)
This paper presents a model for an electronic medical record which satisfies the requirements for a faithful and structured record of patient care set out in a previous paper in this series. The model underlies the PEN & PAD clinical workstation, and it provides for a permanent, completely attributable record of patient care and the process of medical decision making. The model separates the record into two levels: direct observations of the patient and meta-statements about the use of observations in decision making and the clinical dialogue. The model is presented in terms of “descriptions” formulated in the Structured Meta Knowledge (SMK) formalism, but many of its features are more general than the specific implementation. The use of electronic medical records based on the model for decision support and the analysis of aggregated data are discussed along with potential use of the model in distributed information systems.
Keywords: Medical Record; Information Models; Standards; Problem-Oriented Medical Record; Coding Systems